2004
DOI: 10.1017/s026988890400013x
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of spatio-temporal database models

Abstract: Recent efforts in spatial and temporal data models and database systems have attempted to achieve an appropriate kind of interaction between the two areas. This paper reviews the different types of spatio-temporal data models that have been proposed in the literature as well as new theories and concepts that have emerged. It provides an overview of previous achievements within the domain and critically evaluates the various approaches through the use of a case study and the construction of a comparison framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 57 publications
0
116
0
5
Order By: Relevance
“…However, carried out literature review [3][4][5] showed that the issues of local spatial inhomogeneities analysis during organization of spatial object monitoring systems haven't been sufficiently addressed so far.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, carried out literature review [3][4][5] showed that the issues of local spatial inhomogeneities analysis during organization of spatial object monitoring systems haven't been sufficiently addressed so far.…”
Section: Problem Statementmentioning
confidence: 99%
“…Several studies have made detailed survey about those spatiotemporal data models [43,48]. In order to effectively incorporate and store dynamic data from different sources, the data model in the DiSTDB is extended from the simple snapshot data model and the object-based spatiotemporal model.…”
Section: The Object-oriented Spatiotemporal Data Modelmentioning
confidence: 99%
“…However, the programmer is limited to accessing data from one point in the animation at a time, and there is no notion of sharing these animations between participants connected by a network. Spatio-temporal databases [28] capture spatial and temporal aspects of data and deal with the position and/or geometry of objects changing over time. Spatio-temporal databases support queries about time, temporal properties, and temporal relationships allowing data to be accessible at any point in time.…”
Section: Other Programming Environments For Managing Timementioning
confidence: 99%